(3aj GdEOGQGJ GdLGeYjIs - (3NGdO GMeO SdGeI(B, (3GdUQGjQIs ((3YeGf(B:s (3OGQ cfhR GdeYQaI(B,s, 2010)
(3GdJYQa Ydi OQLI GdJeGKd GdJfXjej dOi GYVGA GdgjFGJ GdJOQjSjI aj GdLGeYGJ GdCQOfjI GdQSejI , h HjGf YdGbJg Hcd ef GdTYhQ HGdCef h GdBOGA GdhXjaj dOjge (B.s
(3eQGLY U(B.149 (3; edGMb U(B.167s
Keywords: (3GdEOGQI(B- (3GdLGeYIs; (3GdGOGA GdhXjajs; (3GdJYdje GdYGdjs; (3GdLGeYGJs